2020
DOI: 10.1155/2020/5215479
|View full text |Cite
|
Sign up to set email alerts
|

Model of Driver’s Eye Movement and ECG Index under Tunnel Environment Based on Spatiotemporal Data

Abstract: In order to improve the driver's physiological and psychological state, the driver's mental load which is caused by sight distance, lighting, and other factors in the tunnel environment should be quantified via modeling the spatiotemporal data. e experimental schemes have been scientifically designed based on methods of traffic engineering and human factor engineering, which aims to test the driver's spatiotemporal data of eye movement and ECG (electrocardiogram) index in the tunnel environment. Firstly, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…A mathematical model of FRSA is formulated based on the CEPO technology, which makes use of the future traffic environment to implement path optimization. Due to the effects of traffic flow, network structure, and driver characteristics, some critical factors like timedependent traffic speeds, network topology, temporal congestion area evolution, different vehicle departure times, vehicle waiting behaviour, and network size are considered in the proposed model [47][48][49]. e objective of the proposed method is to minimize the sum of the delivery costs, such as travelling time and path length.…”
Section: Discussionmentioning
confidence: 99%
“…A mathematical model of FRSA is formulated based on the CEPO technology, which makes use of the future traffic environment to implement path optimization. Due to the effects of traffic flow, network structure, and driver characteristics, some critical factors like timedependent traffic speeds, network topology, temporal congestion area evolution, different vehicle departure times, vehicle waiting behaviour, and network size are considered in the proposed model [47][48][49]. e objective of the proposed method is to minimize the sum of the delivery costs, such as travelling time and path length.…”
Section: Discussionmentioning
confidence: 99%
“…The distance sign was set on either the left or right side of the tunnel wall. According to the dynamic FOV theory [19,[46][47][48], when the driving speed is 80 km/h and the human head and eyeballs remain motionless, the driver's FOV is 58°; therefore, the longitudinal distances between the left and right tunnel walls and the vehicle were 6 m and 14 m, respectively. According to the research of ergonomic visual characteristics, the area 10° above and below the visual horizon is the best visual area of the human eye in the vertical direction.…”
Section: ) Setting Methods Of the Distance Signmentioning
confidence: 99%
“…Verwey [ 6 ] found that the closer to the tunnel a driver is, the lower the number of human gazes and the scanning range will be. Qi [ 7 ] and Yang [ 8 ] tested the driver’s eye movement data in the tunnel environment. Ye [ 9 ] conducted a driving simulation test, and the pupil diameter and the sight deviation time were analyzed.…”
Section: Literature Reviewmentioning
confidence: 99%